Meningkatkan Kemampuan Berkomunikasi Anak Melalui Metode Cerita Bergambar pada PAUD Kelompok B - Abdul Syukur; Meo Melianus Tefanai (Universitas Trunojoyo Madura, 2017)
The aim of this research is to improve the communication skills of children through the method of pictorial stories applied to group B ECD Gemilang in the District of Maulafa, Kota Kupang. This is a type of Classroom Action Research that consists of four stages in each cycle, they are: planning, implementation, observation and reflection. The main focus of this research is to improve children's skills and ability to communicate through this pictorial story method. Nineteen children have been included in this study and the data has been collected through observation and tests. The results show that the average score of pre-cycle is 37.57%, the one of the first cycle is 57.89% and 100% is the average score achieved in the second cycle. Looking at these results, it can be stated that using pictorial stories in a learning process can improve children’s communication skills and ability.